Pengaruh Debt Ratio, Long Term Debt to Equity Ratio dan Kepemilikan Institusional Terhadap Return on Asset pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Jufrizen, Jufrizen; Putri, Aghnia Meilana; Sari, Maya; Radiman, Radiman; Muslih, Muslih (JURNAL MANAJEMEN MOTIVASI, 2019)
This study aims to determine the effect of Debt Ratio, Long Term Debt to Equity Ratio, and Institutional Ownership on Return On Asset both partially and simultaneously in the Food and Beverage Sub-Sector companies listed on the Indonesia Stock Exchange. The approach used in this study is an associative approach. The population in this study were eighteen companies and thirteen companies were used as samples in the Food and Beverage Sub-Sector listed on the Indonesia Stock Exchange and components and observations made over five years starting from 2013-2017. Data collection techniques in this study used multiple regression analysis. The results of this study prove that partially or simultaneously Debt Ratio, Long Term Debt to Equity Ratio, and Institutional Ownership have no significant effect on Return On Assets in companies in the Food and Beverage Sub-Sector listed on the Indonesia Stock Exchange for the period 2013-2017.